ANALYSIS OF MATHEMATICS SUMMATIVE EXAMINATION PROBLEMS IN CLASS VII OF SMP NEGERI 2 NGANTANG USING ANATES - Kholil, Mohamad; Faradiba, Surya Sari (JME (Journal of Mathematics Education), 2024)
This study aims to: (1) describe the level of difficulty, discriminatory power, and the effectiveness of distracting items on Year-End Assessment of mathematics using Anates software in class VII SMP Negeri 2 Ngantang, (2) describe the percentage quality of difficulty level, discriminating power, and The effectiveness of the item distractor on Year-End Assessment of mathematics subject using Anates in class VII of SMP Negeri 2 Ngantang. This study uses a qualitative approach. The data source used is a secondary data source. The data collection technique used is documentation. The research data was then analyzed using Anates software. The results showed that overall the items were quite valid, the reliability was high, the average level of difficulty was moderate but not balanced, the proportion of easy to medium difficulty should be 4 – 4 - 4 or 4 - 4 -5 - 3, the discriminating power of all questions was accepted, the distractor was generally effective, only 2 out of 36 or 5.56% that were badly needed to be replaced, while the significance of the items was 7 out of 12 questions or 57.33% significant.